Sulh dalam perundangan islam: analisis literatur utama / Hadenan Towpek & Ahmad Shah Affandie - Towpek, Hadenan; Affandie, Ahmad Shah (Majmuah Enterprise dan UiTM Sarawak, 2023)
Nowadays Sulh is one of the methods of Alternative Dispute Resolution (ADR) which is much appreciated in Malaysia, especially in the Syariah Court. Therefore, this article analyses the contract of Sulh with special concern on its definition, concept, theory, approaches, and application in Islamic legislation. The study applies three categories of previous literature sources, namely 8 sources of open literature, 19 sources of notable literature, and 12 official sources from agencies with jurisdiction in Shariah law in Malaysia. The result of this study provides a summary of the main finding which is the method of sulh has been successfully developed based on sources from the Qur’an, al-Sunnah, and the treasures of Islamic jurisprudence.